Knowledge Management - Szöke, Linda (My University, 2009)
In light of globalisation an intensive global competition has evolved amongst corporations and companies, which have started extending their activities to the international market by establishing more and more subsidiaries all over the world. On the other hand, these extensions have generated problems for managers as their departments and units have got to be diversely located geographically and they have to find a solution for transferring knowledge, the core competences of the organization within their departments, units and teams to sustain the business activities and operations. To bridge over the geographical distance, people within organization have started using non-face-to-face technological (ICT) tools to be able to discuss problems, requests, solutions and develop business solutions or solve tasks were required in different places at the same time. The aim of this thesis is to create a theoretical framework to answer the questions how people use ICT tools for tacit knowledge sharing and which factors influence how actually these tools are used. The framework is built on the results of the inductive study. This study is conducted as a qualitative case study by interviewing nine members of the Hungarian department. The empirical research pointed out that the tacit knowledge sharing through ICT tools (especially email, instant messaging and telephone) within the case company is influenced by organizational, social, relational context and characteristics of ICT tools.
Keywords: Tacit Knowledge Sharing; ICT (Information and Communication